2019
DOI: 10.1108/qae-05-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic model of student satisfaction: a viewpoint of private higher education

Abstract: Purpose-The purpose of this paper is to investigate the relationship between service quality, program quality, institutional image and student satisfaction in the context of higher education. Additionally, the study attempts to describe the mediating impact of institutional image between service quality, program quality and student satisfaction. Design/methodology/approach-The structural equation modeling was used to analyze the influence of mediating variable and hypotheses testing. The population of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 89 publications
3
57
0
1
Order By: Relevance
“…Students have high expectation on the quality of teaching lecturers so that they can improve their learning result Students will be more enthusiastic in lectures and completion of studies. The results of the study supported the results of previous studies which found a positive and significant effect on student satisfaction (Butt & Rehman, 2010;Carter & Yeo, 2016;Fernandes et al, 2013;Isnaini et al, 2015;Martirosyan, 2015;Osman & Saputra, 2019;Putri, 2018;Rahmawati, 2013;Sabihaini & Satoto, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Students have high expectation on the quality of teaching lecturers so that they can improve their learning result Students will be more enthusiastic in lectures and completion of studies. The results of the study supported the results of previous studies which found a positive and significant effect on student satisfaction (Butt & Rehman, 2010;Carter & Yeo, 2016;Fernandes et al, 2013;Isnaini et al, 2015;Martirosyan, 2015;Osman & Saputra, 2019;Putri, 2018;Rahmawati, 2013;Sabihaini & Satoto, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Fernandes, Ross, & Meraj (2013) found that the quality of lecturers became the main reason of student satisfaction. Osman & Saputra (2019) confirmed that the teaching method used by lecturers can be seen as an indicator of program quality in which it has a significant effect on student satisfaction. Teaching staff with a higher level of commitment to the student learning experience proved to have a significant influence on student satisfaction (Poon & Brownlow, 2015).…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Competition for students among the many higher educational institutions has made customer satisfaction a paramount concept in the field of education (Osman & Saputra, 2019), and customer satisfaction is said to be a strategic tool towards achieving customer retention and loyalty (Agyei & Kilika, 2013;Zhen, Cao, & Tang, 2018). Kaur and Bhalla (2018) argued that students are the internal customers of educational institutions and as such, policymakers should yearn to satisfy their students since dissatisfaction ranks among the causes for high attrition rate among distance students (Jan, 2015).…”
Section: Introductionmentioning
confidence: 99%